The historian's toolbox - Williams, Robert C., author. Link
1 online resource (xiv, 230 pages).
Keywords: Now in its fifth edition, The Historian's Toolbox is designed to help students become skilled in the intellectual process and craft of history, offering an overview of the field and techniques for reading and writing about history. The fifth edition expands the selection of tools available to students entering the workshop of history. These include new chapters on digital history, Indigenous peoples, and gender history and new sections on the Voynich manuscript, LGBTQ+ history, slavery, and a historian who survived the war in Ukraine. The book has been fully updated to address the possibilities and limits of computerized approaches to doing history, with careful attention paid to the benefits and controversies of artificial intelligence, chatbots, and the internet. It demonstrates the continuing relevance of history in a cacophonous world of misinformation and censorship, emphasizing critical thinking, facts, and evidence as valuable means of understanding the past and shaping the future. Engaging and accessible, this volume is ideal for undergraduate courses in historiography and historical methods.